(untitled) (The Journal of Medicine, Humanity and Media, 2026)
Inequalities in health information access represent a critical driver of global health disparities. This paper examines the theoretical and practical contributions of Professor Gary L. Kreps, a pioneering figure in health communication scholarship. Through analysis of his work on patient empowerment, information-seeking behaviors, and vulnerable populations, this study illuminates Kreps’s communication-centric approach to healthcare practice. The analysis demonstrates that enhancing provider-patient interaction, building health literacy, and addressing the digital divide are essential components of communication empowerment. These insights provide a theoretical framework for reducing health inequalities and advancing equity through strategic communication interventions.